On boundary spanners and interfirm embeddedness: The role of guanxi institution in China. Issue 1 (January 2021) - Cai, Shaohan; Jun, Minjoon; Wang, Xiaoyan; Yang, Zhilin
Abstract: Based on social embeddedness theory and institutional theory, we construct a research model that depicts how boundary spanners' personal relationships affect dyadic embeddedness at the organizational level, under the varying influence of guanxi institution across different regions in China. We empirically test our model by analyzing data collected from 225 retail gas stations within the distribution network of a major Chinese petroleum company. Our analysis shows that boundary spanners need to first establish relational ties, which, in turn, influence interfirm dyadic embeddedness. Additionally, the results indicate that the informal institutions, such as guanxi in China, exert an indirect effect on personal trust through personal closeness. The informal institutions also moderate the effects of personal level trust on organizational level trust, which is a key linkage between personal relationship and interfirm embeddedness. Highlights: A multidimensional interpersonal embeddedness concept is constructed. Boundary spanners need to establish relational ties between themselves, which subsequently affect interfirm embeddedness. The informal institutions (guanxi in China) moderate the impact of personal level trust on organizational level trust. Guanxi institution directly facilitates the establishment of personal closeness between boundary spanners.